2020
DOI: 10.3390/mi11030267
|View full text |Cite
|
Sign up to set email alerts
|

An Electret-Augmented Low-Voltage MEMS Electrostatic Out-of-Plane Actuator for Acoustic Transducer Applications

Abstract: Despite the development of energy-efficient devices in various applications, microelectromechanical system (MEMS) electrostatic actuators yet require high voltages to generate large displacements. In this respect, electrets exhibiting quasi-permanent electrical charges allow large fixed voltages to be integrated directly within electrode structures to reduce or eliminate the need of DC bias electronics. For verification, a − 40   V biased electret layer was fabricated at the inner surface of a silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…To generate considerable SPLs and balance the above-mentioned constraints, several approaches in terms of device structure and driving voltage have been applied in the development of electrostatic MEMS speakers [ 9 , 38 , 90 , 91 , 92 ]. One approach to improve SPL is to use multiple speakers, i.e., array structures.…”
Section: Development Of Mems Speakersmentioning
confidence: 99%
See 2 more Smart Citations
“…To generate considerable SPLs and balance the above-mentioned constraints, several approaches in terms of device structure and driving voltage have been applied in the development of electrostatic MEMS speakers [ 9 , 38 , 90 , 91 , 92 ]. One approach to improve SPL is to use multiple speakers, i.e., array structures.…”
Section: Development Of Mems Speakersmentioning
confidence: 99%
“…To reduce or eliminate the DC bias of electrostatic MEMS speakers, electrets embedded with quasi-permanent electrical charges have been integrated within the electrode structures. In 2020, Sano et al presented an electret-augmented electrostatic MEMS speaker and demonstrated its sound generation under low driving voltages [ 92 ]. The schematic and an SEM image of the fabricated MEMS speaker are shown in Figure 15 e,f, respectively.…”
Section: Development Of Mems Speakersmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the development of energy-saving devices in various fields, MEMS electrostatic actuators still require high voltages to produce large displacements [119]. Electrostatic scratch drive actuators provide low-power, high force actuation but require power supplied by RF [120] or substrate [121] sources.…”
Section: Scratch Drive Actuatormentioning
confidence: 99%
“…5 Recently, a vibration-powered microelectromechanical generator with a potassium-ion electret has attracted increasing attention. [6][7][8][9][10][11] A potassium-ion electret can be fabricated by adding potassium atoms to amorphous silica (a-SiO2) and then subsequently removing them. A potassium-ion electret can permanently store a negative charge, and this enables the creation of maintenance-free power-generation devices.…”
mentioning
confidence: 99%